Molecular detection of Paracoccidioides spp. in environmental samples from the Southwestern Amazon - Ferreira, Iasminy R. Silva; de M. Teixeira, Marcus; de Araújo, Atilon V.; Bagagli, Eduardo [UNESP]; Garces, Hans G. [UNESP]; Peters, Leila P.; Carvalho, Clarice M. (Springer Nature, 2024)
Paracoccidioidomycosis is an infection with the potential for environmental dissemination, especially in regions of hot and humid climate, where human cases have been recorded in the Southwestern Amazon of Brazil, specifically in the state of Acre. Despite studies providing information about the presence of these fungi in soil and animal samples, such as armadillos, further investigations are still needed to determine the epidemiological distribution of the genus Paracoccidioides. The aim of this study was to detect the occurrence of Paracoccidioides fungi in the Southwestern Amazon. To achieve this, 60 soil samples were collected from armadillo burrows on rural properties in the in the municipalities of Acrelândia, Bujari, Plácido de Castro, Rio Branco, Sena Madureira, and Senador Guiomard, located in the state of Acre, Brazil. Fungal DNA was extracted from these samples using the DNEASY® PowerSoil kit—Quiagen, followed by Nested PCR technique with ITS4 and ITS5 as external primers, and PBITS-E and PBITS-R as internal primers. DNA amplification products of about 380 bp compatible with Paracoccidioides spp. were detected in six samples (10%), being sequenced and identified as P. brasiliensis. These findings indicate that the soils of the Acre state could be considered a potential source for Paracoccidioides spp., suggesting that local infections are likely.
Keywords: Acre; Armadillo; Brazil; P.brasiliensis; Paracoccidioidomycosis